Study on insect pest diversity and their risk management options in potato among extension personnels of Bangladesh - Nasif, Saifullah Omar; Hasan, Mahmudul; Islam, Md Saiful; Nitol, Rakibul Hasan; Sajeduzzaman, Md; Ali, Md Razzab (Fundamental and Applied Agriculture, 2018)
The study was conducted in 20 upazila of 10 selected major potato growing districts of Bangladesh to find out the present status and diversity of insect pests of potato, their risks and management options. The data were collected through interview of 60 extension personnels of Department of Agricultural Extension (DAE). BARI Alu-7 (Diamant) variety and BARI Alu-8 (Cardinal) variety of potato were the most popular potato varieties used by the farmers for cultivation. Among the problems for potato cultivation, lower market price ranked the first position. Other major problems faced during potato cultivation were diseases, insect pest attack and weed infestation. The BARI Alu-7 (Diamant) and BARI Alu-8 were the most susceptible potato varieties in terms of insect pests and diseases, whereas the Lal-pakhri was the least susceptible to pest attack. Mostly (98.50%) the potato was infested in the field by cutworm, aphid, potato tuber worm, leaf miner, mole cricket, field cricket and leaf hoppers. Among these insect pests, cutworm and aphid were identified as the major pests and caused damage with high and moderate infestation intensity, respectively. Rat was found as the major pest in storage. The potato tuber worm attacked potato tubers in storage mostly (73.50%) and designated as a major insect pest of potato in storage and damaged potato with high infestation intensity. Spraying of insecticides on the stand- ing potato field is the main control option among farmers to check the pest attack in potato field. Other important control options were application of flood irrigation and hand picking particularly for controlling cutworm, use of granular insecticides in furrows during planting of seed tubers. Most (95%) of the farmers received assistance and advices for controlling insect pests of potato from pesticide dealers. Other sources of services were DAE officials, neighboring farmers and NGO officials. So, emphasis should be given on finding higher value market price for potato as well as safe culti- vation through proper control measure upon consultancy with respective personnel.